Perkahwinan antara agama menurut hukum Islam dan undang-undang keluarga di Indonesia - Amir Husin Mohd Nor ,; Atras Muhammad Zin, (Fakulti Undang - Undang, 2001)

(untitled)
This article seeks to explore the problem of inter-religious marriage in the Muslim community in Indonesia. The main discussion of this article is focused on the legal aspect of inter-religious marriage provided by various family law provisions in Indonesia. Apart from that, the opinion of the Muslim scholars on the subject of inter-religious marriage from the Islamic perspective is also discussed